Dynamics of a lattice gauge theory with fermionic matter—minimal quantum simulator with time-dependent impurities in ultracold gases. (7th August 2018) - Smith, Adam; Kovrizhin, Dmitry L; Moessner, Roderich; Knolle, Johannes
Abstract: We propose a minimal model to study the real-time dynamics of a Z 2 lattice gauge theory (LGT) coupled to fermionic matter in a cold atom quantum simulator setup. We show that dynamical correlators of the gauge fields can be measured in experiments studying the time-evolution of two pairs of impurities, and suggest the protocol for implementing the model in cold atom experiments. Further, we discuss a number of unexpected features found in the integrable limit of the model, as well as its extensions to a non-integrable case. A potential experimental implementation of our model in the latter regime would allow one to simulate strongly-interacting LGT beyond current capabilities of classical computers.